2007
DOI: 10.1300/j083v49n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Living on the Margins

Abstract: A handful of scholars have acknowledged that, along side the traditional homeless, there are now older people who become homeless for the first time in old age. Few researchers, however, have systematically compared the recent older homeless with the chronic or traditional homeless. In the research presented here, we compare recent older homeless with long-term older homeless adults in Toronto according to their health and wealth, their housing history, and their use of health and social services. Findings ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 49 publications
2
14
0
2
Order By: Relevance
“…Previous studies have found that chronically homeless older persons often report histories of mental illness, addictions, unemployment, and other personal barriers that make it hard to maintain stable housing (Cohen, 1997;Crane et al, 2005;Crane and Warnes, 2010;McDonald et al, 2007). A recent body of literature has also focused on growing rates of homelessness among seniors who have lost their housing for the first time in older age Warnes, 2001, 2007;McDonald et al, 2007;Rota-Bartelink and Lipmann, 2007). This area of research has received greater attention in light of trends in population aging and the recent global economic crisis, in which many seniors in North America lost a portion of their pension and retirement savings (Pynoss and Liebig, 2009).…”
Section: Understanding Homelessness Health and Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have found that chronically homeless older persons often report histories of mental illness, addictions, unemployment, and other personal barriers that make it hard to maintain stable housing (Cohen, 1997;Crane et al, 2005;Crane and Warnes, 2010;McDonald et al, 2007). A recent body of literature has also focused on growing rates of homelessness among seniors who have lost their housing for the first time in older age Warnes, 2001, 2007;McDonald et al, 2007;Rota-Bartelink and Lipmann, 2007). This area of research has received greater attention in light of trends in population aging and the recent global economic crisis, in which many seniors in North America lost a portion of their pension and retirement savings (Pynoss and Liebig, 2009).…”
Section: Understanding Homelessness Health and Agingmentioning
confidence: 99%
“…Current research from across North America indicates the homeless population is broadening in its composition to include members of various social groups and age cohorts (Crane and Warnes, 2010;Cronely, 2010;Daly, 1996;DeVerteuil et al, 2009;Lee et al, 2010;Meanwell, 2012). While many studies point to growing numbers of homeless youth (Gaetz et al, 2013a(Gaetz et al, , 2013bKlodawsky et al, 2006;Rachlis et al, 2009), almost an equal share of researchers project increasing numbers of older homeless persons in their senior and elderly years (Cranes andWarnes, 2007, 2010;Kushel, 2011;McDonald et al, 2007McDonald et al, , 2009. Within this literature, experts generally point to two different subgroups, including both older persons who experience housing loss for the first time in their senior years (Crane et al, 2005) and those who have long histories of chronic homelessness Warnes, 2001, 2007;McDonald et al, 2007;Rota-Bartelink and Lipmann, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohen et Crane (1996) font la même constatation dans leur étude menée à Londres et New York. Les taux de prévalence de l'itinérance chez les femmes âgées auraient considérablement augmenté dans les dernières décennies, laissant ainsi entendre qu'il y aurait aussi une augmentation du nombre de PaI « récentes » (mcdonald et al, 2007 ;Kutza et Keigher, 1991). malgré le faible nombre d'études réalisées auprès des PaI, déjà nous pouvons constater que ce groupe est hétérogène.…”
Section: Notentunclassified
“…: SPLI) que par les milieux médicaux et le grand public, comme un déficit personnel, souvent lié à des problèmes de santé mentale ou de toxicomanie (Belcher et al, 2005). Pourtant, de nombreuses recherches sociales démontrent que l'itinérance est le résultat d'une combinaison de facteurs certes individuels, tels que les maladies mentales ou physiques ou l'alcoolisme (Crane, 2001), mais également de facteurs structurels, tels que la perte des prestations d'aide sociale, l'absence de logements abordables ou l'augmentation des loyers, les politiques de désinstitu-tionalisation et les reconfigurations familiales (McDonald et al, 2007 ;Roy et Huturbise, 2007 ;Laberge et al,1998). Les réponses politiques en matière d'itinérance que véhiculent ces représentations ont pour effet de faire porter aux individus le blâme pour leur situation de dépen-dance, contribuant ainsi à l'exclusion symbolique des personnes âgées, des personnes itinérantes et, a fortiori, les PaI.…”
Section: L'exclusion Symbolique Et Institutionnelle Des Pai Une Doublunclassified